BLENDED LEARNING AND LOCALNESS: THE MEANS AND THE END - Mayadas, Frank; Picciano, Anthony G. (Online Learning, 2007)
Blended learning can be seen as the means to achieving a greater sense of “localness” on the part of colleges and universities. Blended learning has been evolving for several years and while definitions vary from one institution to another, it is defined in this paper essentially as a combination of face-to-face and online learning. Localness is a term used at the Alfred P. Sloan Foundation as part of a new funding initiative to support academic programs designed to strengthen a college or university connection to its core constituencies. The purpose of this paper is to explore the relationship of blended learning and “localness”.